The Mongol Cultural Legacy in East and Central Asia: The Early Ming and Timurid Courts. (3rd July 2018) - Shea, Eiren L.
Abstract : Following the fall of the Mongol Empire (c. 1206–1368) in both East and West Asia, Zhu Yuanzhang (Hongwu Emperor, r. 1368–1398), the founder of the Ming Dynasty (1368–1644) in China, Timur (r. 1370–1405), founder of the Timurid Empire (1370–1507) in Central Asia, and their successors used the legacy of the Chinggisid Mongols in different ways to lend an aura of power and legitimacy to their newly established courts. In this paper, I explore the cultural legacy of the Mongol Empire as manifested in the early Ming and Timurid courts, with a special interest in how continuing cultural exchange between the two courts impacted the arts produced in both places. In particular, I highlight how the ongoing incorporation of "foreign" motifs and techniques set the tone for the arts of both courts in the late fourteenth century.